ABUNDANCE AND SPECIES RICHNESS OF LOMBRIC MACROFAUNA IN A SEMI-ARID FOREST ECOSYSTEM - Ababsa, N.; Laiche, A.; Djabbar, F. (University of Eloued جامعة الوادي, 2017)
The importance of earthworms for soils has evolved over time. Our study was conducted in the forest of Ouled yagoub (North East Algerian). Sampling at three different altitudes resulted in a total of forty-nine individuals (49) and only three species were identified: Octodrilus complanatus, Allolobophora molleri and Aporrectodea rosea. Spread over two ecological categories. The specific richness is higher in the site of 1400 m of altitude. The Simpson index (Is) varies between 0.44 and 0.49 for the three study sites. The Shannon index fluctuates between 0.41 and 0.74. The values of the Hill index vary between 1 and 1.5 in the three Sites.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: Abundance; earthworm; species richness; biodiversity.